Pseudorabies virus as a zoonosis: scientific and public health implications - Chen, Yumei; Gao, Jie; Hua, Rongqian; Zhang, Gaiping (Virus genes, 2025)
Pseudorabies virus (PRV) is a herpes virus, also known as Aujeszky’s disease virus (ADV), which can cause a highly infectious disease pseudorabies (PR) in a variety of mammals. In the past, it has been debated whether PRV can infect humans, but more and more cases of PRV infection have been reported since 2017. The illness has claimed many victims and left survivors with serious sequelae. This indicates that humans may ignore the zoonotic ability of PRV. This review aims to summarize the pathology and pathogenesis of PRV and speculate on how it infects humans. This paper provides a comprehensive overview of the progression of PRV, including its virology characteristics, genomic organization, and genetic evolution. It also synthesises the existing literature on PRV infection in humans, and analyses the factors contributing to PRV zoonosis. Finally, the pathogenesis of PRV-infected pigs and other mammals was summarized, and the pathogenesis of PRV-infected humans was speculated.